Caracterización diagnóstica inicial de pacientes con tromboembolismo pulmonar. servicio de urgencias. Hospital Carlos Andrade Marín, 2020–2021 - Valle Noboa, Angela Gabriela (2021)
ABSTRACT Introduction: Pulmonary thromboembolism is a pathology caused by the partial or total obstruction of the vascular lumen in the pulmonary vessels. This thrombus travels mostly from the lower limbs, the initial clinical picture is essential for the diagnosis and prioritization of patients. Objectives: The main initial diagnostic characteristics of patients with pulmonary thromboembolism will be determined in the Emergency Department of Carlos Andrade Marín Hospital, in the period April 2020 April 2021. Material and methods: This study will use the observational, comparative and descriptive, cross-sectional, non-experimental method through information obtained from medical records, will study the initial charts of 278 patients with suspected pulmonary thromboembolism. Results: The predominant clinical picture in patients with pulmonary thromboembolism is pain in lower limbs 50%, dyspnea 49. 1%, desaturation 32. 7%, and chest pain 32. 7% in addition to a history of deep vein thrombosis with a predominance of 32. 73.Conclusions: The main clinical characteristics of pulmonary thromboembolism are pain in lower limbs, dyspnoea, desaturation, and chest pain, personal pathological history such as deep vein thromboembolism, active cancer, previous falls, and bedridden patients are of utmost importance when this disease is suspected. Angiotac is the Gold standard PET tool used after a good medical history, and physical exam Keywords: Pulmonary thromboembolism, initial diagnosis, deep vein thrombosis, Wells scale, emergency department Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258